Assessing disease severity by hsCRP as a biochemical marker for psoriasis - Jain, Kriti; Krishna, Arvind; Rathore, B. S. (International Journal of Research in Dermatology, 2017)
Background: For a complex chronic disease like psoriasis, having a biomarker to objectively assess the clinical severity can be very helpful in disease management. Methods: In a hospital based prospective study, 70 patients of psoriasis diagnosed clinically, were studied. The extent of disease severity was assessed using PASI and BSA and patients were grouped into having mild, moderate and severe disease using these scores. Serum high sensitivity C-reactive protein (hsCRP) levels were then estimated for each group. Results: Of the 70 psoriasis cases enrolled, 46 patients were male and 24 females. Patients with early onset psoriasis were associated with higher values of hsCRP than those with late onset (r=-0.063; p=0.012). A positive correlation was seen between the PASI score and hsCRP levels (r=0.891; p≤0.001). On comparing mean PASI and mean hsCRP in severity groups (mild, moderate and severe), hsCRP was higher in the group with maximum severity (p≤0.001). Conclusions: A negative correlation between the age of onset and hsCRP implies that, earlier the age of onset, higher is the value of hsCRP. Our study shows a positive correlation between the body surface area and PASI score both of which varied linearly with hsCRP values. The findings also suggest that patients with severe psoriasis have higher mean serum hsCRP levels than patients with mild psoriasiss.We proposed hsCRP as a useful marker of psoriasis severity that could be used to monitor psoriasis and, together with PASI, as a global index of disease severity.